Dollarization, inflation and interest rate in Nigeria - David O. Olayungbo; Kehinde T. Ajuwon (CBN Journal of Applied Statistics, 2015)
This paper investigates the relationship among dollarization, inflation and interest rate in Nigeria for the period 1986-2015Q1. It adopts inter-temporal model of money-in-utility (MIU) with an estimation technique of structural vector autoregression (SVAR). Empirical evidence shows that dollarization index has been on the increase in Nigeria since 1994, despite stable and low inflation and interest rate. Results of the cointegration show long run equilibrium among dollarisation, inflation and interest rate. The Granger causality test reveals that there is a unidirectional relationship from dollarization to inflation in Nigeria. This suggests that policies that aim to reduce inflation in Nigeria must include measures that specifically address the issue of dollarization.
Keywords: E44; D9; E5; 330; Dollarization; Inflation; Interest rate; SVAR; Nigeria